Can The Presence of Women in Corporate Governance Reduce Earnings Management Practices? - Windy Aulia Anggranee; Nico Alexander (Global Financial Accounting Journal, 2023)
Purpose - The purpose of this study is to obtain empirical evidence the existence of woman in corporate governance has an influence on the earnings management practice in the company. The independent variables used in this study consisted of woman board of commissioners, woman board of directors, woman audit committee. The role of female in corporate governance is expected to minimize earnings management practices because women have more rational thoughts than men. This rational thinking will reduce the practice of earnings management in the company. Research Method - The study uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the period 2018-2020. The number of samples used in the study were 119 companies with a total of 357 research data. The sampling method used purposive sampling and multiple regression analysis was used to test the hypothesis. Findings - The result show that woman in corporate governance mechanism cannot minimize earnings management, because number of female in corporate governance mechanism in Indonesia still little compare to number of male in corporate governance. Implication - Women who have good supervision and strong ethics of regulations are expected to reduce manipulation in financial statements if women are given equality in decision making, duties and responsibilities in governance so that companies can consider the position of women as supervisors and executors of operations in the company.